2018
DOI: 10.1371/journal.pone.0203006
|View full text |Cite
|
Sign up to set email alerts
|

Substantial improvement of toyocamycin production in Streptomyces diastatochromogenes by cumulative drug-resistance mutations

Abstract: Toyocamycin is a member of the nucleoside antibiotic family and has been recognized as a promising fungicide for the control of plant diseases. However, low productivity of toyocamycin remains an important bottleneck in its industrial production. Therefore, dramatic improvements of strains for overproduction of toyocamycin are of great interest in applied microbiology research. In this study, we sequentially selected for mutations for multiple drug resistance to promote the overproduction of toyocamycin by Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In our previous work, we demonstrated that the triple mutant SD3145 produced a higher yield (1959 mg/L) of toyocamycin, which was 11-fold greater than that produced by the wild-type 1628. In addition, this mutant grew slowly [17]. In general, drug resistance is obtained accompanied by cost of growth fitness.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work, we demonstrated that the triple mutant SD3145 produced a higher yield (1959 mg/L) of toyocamycin, which was 11-fold greater than that produced by the wild-type 1628. In addition, this mutant grew slowly [17]. In general, drug resistance is obtained accompanied by cost of growth fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Realtime quantitative PCR (qRT-PCR) was carried out using an Applied Biosystems StepOne-Plus Real-Time PCR System with FastStar Universal SYBR Green Master (Rox) (Roche) [17]. The gene primers used in qRT-PCR reactions are listed in S1 Table. For each gene, all PCR reactions were carried out in triplicate within a single plate, with rpoA used as the reference gene.…”
Section: Transcription Analysis By Real-time Qpcrmentioning
confidence: 99%
See 3 more Smart Citations